The Influence of Structured Debate Method on Students’ Critical Thinking Skills and Understanding of Islamic Creed in the Study of Ahlusunnah wal Jamaah - Karmani, M. Ali; Gozali, Ahmad (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2025)
The integration of the structured debate method in Islamic theology education remains underexplored, despite its potential to enhance students’ critical thinking and deepen their understanding of Islamic creed, particularly within the Ahlusunnah wal Jamaah (Aswaja) framework. This study aimed to examine the impact of the structured debate method on (1) students’ critical thinking skills and (2) their comprehension of Islamic creed (Aqidah) among second-semester students in the Islamic Education Management Program at STIT Palapa Nusantara. Utilizing a quantitative approach with a pre-experimental design (one-group pre-test and post-test), the study involved 35 purposively selected students. Data were gathered through structured questionnaires and analyzed using paired sample t-tests and correlation analysis. The findings indicate that the structured debate method significantly improved students’ critical thinking skills (p < 0.05) and positively influenced their understanding of the Aswaja creed. These results align with constructivist pedagogical theory, emphasizing the role of interactive learning in promoting cognitive engagement and theological internalization. The study contributes to the theoretical discourse in Islamic education and offers practical guidance for educators and institutions to incorporate structured debate as a strategy to enhance students’ intellectual and spiritual development. Further research is recommended to assess the long-term effects and broader applicability of this method across other areas of Islamic studies.